Indigenous school education as contested spaces: The Brazilian experience in São Paulo and Mato Grosso do Sul - Antonio Augusto Rossotto Ioris; Flávia Vitor Longo; Roberto do Carmo; Jose Mauricio Paiva Andion Arruti (The Australian Journal of Indigenous Education, 2022)
Indigenous schools are spaces for the convergence of different worldviews and to demonstrate how the creativity of each ethnic group challenges exogenous and established concepts and methodologies. This article examines main trends and pending gaps related to indigenous education in Brazil between the years 2007 and 2019. Issues such as the characterisation of indigenous schools, teachers and students are analysed, with a focus on the evolution of the number of students enrolled, infrastructure, language and pedagogic approaches. The analysis is focused on the states of Mato Grosso do Sul, which has a large indigenous population and an economy based on export-oriented agribusiness, and São Paulo, the main economic, demographic and political centre of Brazil with a much smaller indigenous population. The results demonstrate concrete improvements, especially the expansion of the number of schools and the student population. A growing number of schools are now dedicated to serve indigenous populations and make use of specific teaching material (although this material is of uneven quality). However, many problems remain unresolved, including threats to funding and uncertain administrative support from public authorities, a situation that has been aggravated in recent years with the growing adoption of elitist, anti-indigenous government policies.